Hypersensitivity pneumonitis in a child (observational data for six years): A clinical case - V. S. Chulkov; L. V. Medvedeva; E. E. Minina; E. V. Fastakovskaya (Кубанский научный медицинский вестник, 2025)
Background. Hypersensitivity pneumonitis refers to a rare interstitial lung disease that requires differential diagnosis with a large spectrum of nosologies. However, the prevalence of hypersensitivity pneumonitis in the population remains unclear, partly due to low awareness among healthcare professionals of various specialties regarding this condition, as well as diagnostic challenges. Many authors emphasize the necessity of a detailed analysis of professional and environmental factors affecting the patient as one of the crucial steps in diagnosing hypersensitivity pneumonitis. The prognosis for hypersensitivity pneumonitis in children is more favorable than in adults, with complete clinical and functional recovery possible in most cases if the causative antigen is eliminated.Case description. The paper presents data from a six-year observation of a 9-year-old girl. Within six months prior to her consultation, she developed respiratory complaints (shortness of breath, respiratory distress, fits of dry coughing), poor tolerance to physical exertion, and chronic weakness. She was monitored and treated for bronchial asthma by a pulmonologist without significant clinical improvement. Subsequently, specialists at a regional center conducted extensive work on differential diagnosis and verification of the disease through meticulous collection of anamnesis and clinical data and the use of modern laboratory and instrumental resources. Effective treatment was selected, and recommendations were given in order to correct influencing factors (change of residence and living conditions). A clear improvement in clinical, laboratory, and instrumental data was demonstrated over the observation period, with significant effects achieved within a year from the start of therapy. Improvements were noted in both volume and flow parameters on spirometry, with no restrictive disorders observed; the most indicative changes were revealed in the dynamics of high-resolution computed tomography.Conclusion. The presented clinical case demonstrates the necessity of paying special attention to thorough history-taking and identifying potential causal factors. A distinctive feature of the disease consists in reversible symptoms, sustained remission, and a favorable prognosis under conditions of timely diagnosis, treatment, and removal of the causal factor.